(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aims at knowing the actual uses of instructional technology in teaching history subject in the colleges of education for humanities from the college staff members’ perspectives and their attitudes towards it. The sample of the study consisted of (24) instructors from the Colleges of Education for the Humanities, the College of Basic Education- Haditha and the College of Education for Women, the study used the descriptive method, and the questionnaire was consisted of (50) items, and the psychometric properties of the instrument of the study were extracted. The researchers used the appropriate statistical means to analyze the data, and the results of the study showed the following: the teaching staff attitudes towards the use of instructional technology in general are acceptable, as the general weighted average reached (2.48), The use of instructional technology gained a weak degree, as the general weighted average reached (1,795), which indicated the scarcity of technologies. The general weighted average of the obstacles that hinder the use of instructional technology reached (2,283), which represents a large degree, and this indicates the large number of obstacles. As for the availability of instructional technology in the scientific departments, the general weighted average reached (1.35), which represents a low degree. In the light of the results of the study the study presented some recommendations and suggestions.